A Farming Community's Perspective on Nutrient Loss Reduction. Issue 1 (1st April 2019) - Marks, Benjamin; Boerngen, Maria A.
Abstract : Core Ideas: Interviews with Illinois farmers revealed they are concerned about nutrient loss. Illinois farmers may not know specifics of the IL Nutrient Loss Reduction Strategy. However, they are changing their practices in response to nutrient loss concerns. Opportunities exist to further encourage adoption of BMPs to meet IL NLRS goals. The Illinois Nutrient Loss Reduction Strategy (NLRS) is a voluntary framework to achieve ambitious reductions in nitrate‐nitrogen and phosphorus runoff to the Mississippi River. In interviews, a group of "conservation‐minded" Illinois farmers revealed that while they are not necessarily familiar with the Illinois NLRS, they are concerned with nutrient loss and are taking steps to address those concerns. However, the strategy's "Phase 1 Milestones" of 15 and 25% reduction in nitrate‐nitrogen and phosphorus loss, respectively, by 2025 may require additional efforts to encourage adoption of the best management practices (BMPs) recommended by the strategy. This study identifies the information sources farmers trust in making management decisions, suggesting avenues to encourage achieving the goals of the Illinois NLRS. It also serves as the pilot study for a large‐scale farmer survey that will provide a more thorough understanding of Illinois farmers' awareness of, and responses to, nutrient loss issues.